Prevalence and correlates of hearing and visual impairments in European nursing homes: results from the SHELTER study - Yamada, Yukari; Vlachova, Martina; Richter, Tomas; Finne-Soveri, Harriet; Gindin, Jacob; van der Roest, Henriëtte; Denkinger, Michael D; Bernabei, Roberto; Onder, Graziano; Topinkova, Eva (Journal of the American Medical Directors Association, 2014)
BACKGROUND: Visual and hearing impairments are known to be related to functional disability, cognitive impairment, and depression in community-dwelling older people. The aim of this study was to examine the prevalence of sensory impairment in nursing home residents, and whether sensory impairment is related to other common clinical problems in nursing homes, mediated by functional disability, cognitive impairment, and depressive symptoms. METHODS: Cross-sectional data of 4007 nursing home residents in 59 facilities in 8 countries from the SHELTER study were analyzed. Visual and hearing impairments were assessed by trained staff using the interRAI instrument for Long-Term Care Facilities. Generalized linear mixed models adjusted for functional disability, cognitive impairment, and depressive symptoms were used to analyze associations of sensory impairments with prevalence of clinical problems, including behavioral symptoms, incontinence, fatigue, falls, problems with balance, sleep, nutrition, and communication. RESULTS: Of the participants, 32% had vision or hearing impairment (single impairment) and another 32% had both vision and hearing impairments (dual impairment). Residents with single impairment had significantly higher rates of communication problems, fatigue, balance problems, and sleep problems, as compared with residents without any sensory impairment. Those with dual impairment had significantly higher rates of all clinical problems assessed in this study as compared with those without sensory impairment. For each clinical problem, the magnitude of the odds ratio for specific clinical problems was higher for dual impairment than for single impairment. CONCLUSION: Visual and hearing impairments are associated with higher rates of common clinical problems among nursing home residents, independent of functional disability, cognitive impairment, and depressive symptoms.
Keywords: Disability Evaluation; Cross-Sectional Studies; poruchy zraku; Nursing Homes; Male; kognitivní poruchy; Risk Factors; nursing home; posuzování pracovní neschopnosti; Europe; prevalence; Aged; dual sensory impairment; mužské pohlaví; senioři; deprese; poruchy sluchu; Evropa; senioři nad 80 let; lidé; Vision Disorders; ženské pohlaví; Humans; Cognition Disorders; rizikové faktory; průřezové studie; Aged, 80 and over; Prevalence; pečovatelské domovy; Hearing Disorders; Female; Depression; Older people; frailty